Nonbank lending and the transmission of monetary policy - Dominic Cucic; Denis Gorea (Danmarks Nationalbank, 2024)
We analyze the role of nonbank lenders in the transmission of monetary policy using data on the universe of unsecured credit to firms and households in Denmark. Nonbanks increase their credit supply after a monetary contraction, both relative to banks and in absolute terms. The nonbank credit expansion is driven by long-term debt funding flowing to nonbanks. The attenuation of the traditional bank lending channel of monetary policy has real effects: nonbank credit insulates corporate investment and household consumption from adverse consequences of monetary contractions.
Keywords: E51; E52; G23; 330; Monetary Policy; Nonbanks; Shadow Banks; Banks; Real Effects